Emission Calculation Methods for Handling Equipment in Inland Container Depots: A Systematic Review and Research Directions - Thi Hoang Thao, Doan; Nguyen Dang Khoa, Pham; Thi Ha, Quach; Linh Chi, Duong; Minh Hieu, Nguyen (Journal of Transportation Science and Technology, 2025)
Emission calculation from handling equipment in inland container depots is crucial for environmental management in logistics operations. This systematic review analyzes 47 high-quality papers selected from 942 initial studies to examine current emission calculation methodologies. Results identify four main approaches: activity-based, simulation-based, direct measurement, and integrated optimization methods. Terminal tractors, RTG/RMG cranes, and reach stackers emerge as primary emission sources. Three significant trends are identified: equipment electrification, integration of emission calculations into terminal planning, and development of standardized toolkits. Key challenges include data quality issues, lack of unified standards, and limited research on pollutants beyond CO₂. The study proposes three future research directions: developing harmonized calculation frameworks that balance universal applicability with local factors, comprehensive characterization of multi-pollutant emission profiles under real-world conditions, and integration of real-time analytics and machine learning for dynamic emission management. These advancements are essential for achieving sustainable terminal operations while maintaining operational efficiency.
Keywords: ICD; Emissions; Handling equipment; Green logistics; Systematic review